Modelado del equilibrio de fases líquido - vapor para la extracción de ácidos grasos con fluido supercrítico - Loyola Carranza, Wilber (2009)
In this thesis work the liquid- vapor equilibrium state of the supercritical carbon dioxide and fatty acids mixtures by means of equations of state has been modeled. Binary mixtures containing carbon dioxide with the following acids: oleic, linoleic, palmitic and lauric acids were considered. Both equations, the Predictive Soave Redlich- Kwong (PSRK) and Perturbed Chain - Statistical Associating Fluid Theory (PC - SAFT) with the van der Waals rules of mixing and two associating sites were used. The optimal parameters of the pure component of the PC- SAFT equation were calculated using both the vapor pressure and saturated liquid density data. The binary interaction parameters required in the rules of mixture of the PC- SAFT equation were determined by minimization of errors between the experimental mol fraction of the carbon dioxide and the calculated ones. For the calculation of the total molar volume of mixture the energy parameter of the PSRK equation joined to the UNIFAC method and the rule of mixture for the volume parameter were used. The results of the liquid - vapor equilibrium state modeling of fatty acids reveal that the predictions of the PSRK equation are better than those of the PC- SAFT one in terms of the average absolute deviations of the molar fraction of the supercritical solvent.